A transient resistance to blood-stage malaria in interferon-γ-deficient mice through impaired production of host cells preferred by malaria parasites - Okada, Hiroko; Suzue, Kazutomo; Imai, Takashi; Taniguchi, Tomoyo; Shimokawa, Chikako; Onishi, Risa; Hirata, Jun; HISAEDA, Hajime (Frontiers in Microbiology, 2015)
IFN-γ plays both pathological and protective roles during blood-stage malaria. One of its pathological roles is its contribution to anemia by suppressing erythropoiesis. Here, to evaluate the effects of IFN-γ-mediated alterations in erythropoiesis on the course of malaria infection, mice deficient in IFN-γ (GKO) were infected with two strains of the rodent malaria parasite Plasmodium yoelii, 17XL (PyL) and 17XNL (PyNL), whose host cell ranges differ. Regardless of genotype, all mice infected with PyL, which can invade any erythrocyte, developed high parasitemia and died quickly. Although PyNL caused a transient non-lethal infection in wild-type (WT) mice, some GKO mice were unable to control the infection and died. However, GKO mice were resistant to the early phase of infection, showing an impaired increase in parasitemia compared with WT mice. This resistance in the GKO mice was associated with having significantly fewer reticulocytes, which are the preferred host cells for PyNL parasites, than the WT mice. Compared with the amount of reticulocytes in GKO mice during the early stages of infection, there was a significant increase in the amount of these cells at later stages, which coincided with the inability of these mice to control the infection. We found that the growth of PyNL parasites correlated with the amount of reticulocytes. Thus, the reduced number of reticulocytes in mice lacking IFN-γ appears to be responsible for the limited parasite growth. Notably, these differences in GKO mice were at least partially reversed when the mice were injected with exogenous IFN-γ. Additionally, an artificial induction of hemolytic anemia and an increase in reticulocytes by phenylhydrazine treatment in GKO mice completely abolished the lower parasitemia and resistance during early phase infection. These results suggest that IFN-γ may contribute to the early growth of PyNL parasites by increasing the amount of reticulocytes, presumably by enhancing erythropoiesis.